Hypnosis as an alternative to general anaesthesia for paediatric superficial surgery: a randomised controlled trial. (March 2023) - Sola, Chrystelle; Devigne, Julie; Bringuier, Sophie; Pico, Julien; Coruble, Lucie; Capdevila, Xavier; Captier, Guillaume; Dadure, Christophe
Abstract: Background: Reducing perioperative anxiety and controlling pain in children are essential to optimise recovery and outcomes for both children and their parents. By acting on sensory and affective modulation of anxiety and pain, hypnosis is widely used in medical care, especially in anaesthesia. This randomised controlled clinical trial was designed to compare general anaesthesia and intraoperative hypnosis support for perioperative management of children undergoing superficial surgery. Methods: Children aged 7–16 yr scheduled for day-case superficial surgery were included and randomly assigned to one of the following two groups: general anaesthesia group or hypnosis group. The primary outcome was length of hospital stay. Child and parent anxiety, child pain, and the occurrence of postoperative negative behavioural changes were also evaluated. Results: Sixty children of mean age 10.3 (standard deviation: 2.6) yr were enrolled in the study. Hypnosis was successful in all but one case. The median (25th–75th percentile) length of hospital stay was shorter in the hypnosis group (120 [95–145] vs 240.5 [218–275] min; P <0.001). The general anaesthesia group was associated with a greater incidence of high levels of preoperative anxiety in children (30 vs 11%; P =0.001) and parents (55 vs 30%; P =0.05). Pain scores did not differ between groups. No negative postoperative behavioural changes were reported. Conclusions: In children aged 7–16 yr, hypnosis appears to be feasible and accepted. The quality of the perioperative experience and the rapid recovery support the use of hypnosis as an effective and safe alternative to general anaesthesia for paediatric superficial surgery. Clinical trial registration: NCT02505880.